Emerging role of HDAC11 in skeletal muscle biology - Chen, Jihong; Li, Qiao (Frontiers in Cell and Developmental Biology, 2024)
HDAC11 is an epigenetic repressor of gene transcription, acting through its deacetylase activity to remove functional acetyl groups from the lysine residues of histones at genomic loci. It has been implicated in the regulation of different immune responses, metabolic activities, as well as cell cycle progression. Recent studies have also shed lights on the impact of HDAC11 on myogenic differentiation and muscle development, indicating that HDAC11 is important for histone deacetylation at the promoters to inhibit transcription of cell cycle related genes, thereby permitting myogenic activation at the onset of myoblast differentiation. Interestingly, the upstream networks of HDAC11 target genes are mainly associated with cell cycle regulators and the acetylation of histones at the HDAC11 target promoters appears to be residue specific. As such, selective inhibition, or activation of HDAC11 presents a potential therapeutic approach for targeting distinct epigenetic pathways in clinic applications.